Analisis Financial Distress Dengan Pendekatan Altman Pada Awal Covid-19 Di Indonesia (Studi Empiris Perusahaan Transportasi dan Logistik Periode 2019) - Nanda Ayu Hafsari; Yulita Setiawanta (Jurnal Akuntansi dan Pajak, 2021)
The purpose of this study is to analyze financial distress with Altman's (Z-Score) approach to transportation and logistics manufacturing companies during the covid-19 pandemic. The financial ratios analyzed are Return On Assets, Return On Equity, Current Ratio, and Debt To Asset Ratio as independent variables and Financial Distress as dependent variables. The population and samples in this study are Transportation and Logistics manufacturing companies listed on the Indonesia Stock Exchange in 2019. The samples in this study used census sampling techniques and were processed using logistic regression analysis. From the results of the study, it shows that the profitability ratio measured by Return On Assets and liquidity ratio measured by current ratio affect the company's financial distress prediction. The profitability ratio measured by Return On Equity and the leverage ratio measured by the Debt To Asset Ratio have no effect on the company's financial distress.